The physical activity level of Mexican children decreases upon entry to elementary school El nivel de actividad física disminuye en niños mexicanos al ingresar a la escuela primaria - Alejandra Jáuregui; Salvador Villalpando; Eduardo Rangel-Baltazar; Jessica Castro-Hernández; Yaveth Lara-Zamudio; Ignacio Méndez- (Instituto Nacional de Salud Pública, 2011)
OBJECTIVE: To compare the physical activity patterns of a cohort of Mexican children in kindergarten (K), first (1ES) and second grade (2ES) of elementary school. MATERIAL AND METHODS: The physical activity of 217 children (123 girls and 94 boys) aged 5-6 years was measured (five full-day triaxial accelerometry) annually.Weekday and weekend moderate/ vigorous physical activity (MVPA) and school and off-school MVPA was calculated. Comparisons between surveys were made using longitudinal multilevel generalized linear models. RESULTS: Weekday MVPA was 22 and 37 min/d lower for 1ES (p=0.06) and 2ES (p<0.01), respectively, compared to K. School MVPA for 1ES and 2ES was 37 (-5.0 min/h) and 40% (-5.5 min/h) (p<0.001) lower, respectively, compared to K. No differences were found between weekend and off-school MVPA among school stages (p>0.5). CONCLUSION: MVPA was significantly reduced from K to ES,in part because of a decline in MVPA during school activities. Interventions targeted to school environment modifications should be promoted. OBJETIVO: Comparar los patrones de actividad física (AF) en una cohorte de niños mexicanos en el jardín de niños, primer y segundo grado de primaria. MATERIAL Y MÉTODOS: Se midió anualmente la AF (acelerometría triaxial de cinco días completos) en 217 niños (123 niñas y 94 niños) de 5 a 6 años de edad. Se calculó la AF moderada/vigorosa (AFMV) entre semana y de fin de semana, dentro y fuera del horario escolar. Se realizaron comparaciones mediante modelos lineales generalizados multinivel longitudinales. RESULTADOS: La AFMV entre semana fue 22 (p=0.06) y 37 min/d (p<0.01) menor, y la AFMV durante el horario escolar disminuyó 37 (-5.0 min/h) y 40% (-5.5 min/h) (p<0.001), en 1º y 2º de primaria,respectivamente,comparado con el jardín de niños.No se encontraron diferencias en la AFMV de fin de semana o fuera del horario escolar entre los grados escolares (p>0.05). CONCLUSIONES: La AFMV disminuyó de manera significativa del jardín de niños a 2º de primaria en parte debido a una reducción de AFMV durante las actividades escolares. Es necesaria la promoción de intervenciones enfocadas a la modificación del ambiente escolar.